EDUCATIONAL VALUES IN THE QURAN SURAH AL-JUM'AH (STUDY OF AL-MISHBAH AND AL-WASITH) - Achyar Zein; Muhammad Al-Farabi; Abdul Roni (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
This study aims to analyze: 1) The content of Islamic education in Surah al-Jumu'ah according to Tafsir Al- Misbah and Al-Wasith, and 2) The values of Islamic education contained in Surah al-Jumu'ah. 3) The relevance of Islamic educational values in surah al-Jumu'ah to contemporary education. This study uses a qualitative method using a library research approach. The primary data sources in this study were the Qur'an al-Karim along with the Tafsir Al-Misbah by M. Quraih Shihab and the Tafsir al-Wasith by Wahbah az-Zuhaily. The results showed that: 1) Interpretation of QS al-Jumu'ah by Tafsir al-Misbah and Tafsir al-Wasith, there were no significant differences of opinion regarding their interpretation of QS al-Jumu'ah. 2) The Values of Islamic Education in Surah al-Jumu'ah described by Tafsir al-Misbah and Tafsir al-Wasith include: a) the Value of Worship: Always glorify Allah SWT. and an appeal to seek knowledge and practice it, b) Moral Values, c) Death Warning, d) Suggestions to leave business during Friday prayers. 3) The educational values described by Tafsir al-Misbah and Tafsir al-Wasith above have relevance. Namely, these values can be implied in contemporary Islamic education, for example, by imitating the Prophet as an educator with excellent affective, cognitive, and psychomotor abilities. According to Islamic teachings, Islamic education is physical and spiritual guidance formed by the primary personality. The educational values contained in the Qur'an Surat Al-Jumu'ah study of Tafsir Al-Mishbah Dan Al- Wasith surah begin with the wisdom of Allah, His glory, and His nature with perfect qualities, then praise the Prophet SAW. Educational values in Surah Al-Jumuah, namely explaining the values of Worship to Allah Almighty, Moral Values, Death Warnings, and Recommendations to Leave Business during Friday Prayers.